Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Mais oui c'est un travail!: penser le travail du sexe au-delà de la victimisation - Parent, Colette; Bruckert, Chris; Corriveau, Patrice; Nengeh Mensah, Maria; Toupin, Louise (Collection Problèmes sociaux & interventions sociales, 2010)
La question du travail du sexe fait toujours, aujourd’hui, l’objet de polémiques où le moralisme et les bons sentiments prévalent sur la discussion ouverte. La traite des femmes pour fins de « prostitution » et leur vulnérabilité physique face à la violence et à l’homicide débouchent souvent sur des demandes de répression accrue, et ce sont les travailleuses du sexe qui font les frais de ces discours prohibitionnistes et moralisateurs. Soucieux de véhiculer auprès d’un large public une vision différente de la « prostitution » dans le respect des travailleuses du sexe et de remettre en question les bases du message néo-abolitionniste qui présente ces dernières essentiellement comme des victimes de souteneurs ou de leur fausse conscience, cinq spécialistes ont entrepris la rédaction collective d’un livre pour démystifier plusieurs préjugés liés au travail du sexe. Sont abordés dans ce livre original les fondements du débat actuel de la « prostitution » comme travail, les différentes réponses des régimes juridiques, la variété de pratiques et d’expertises mises en oeuvre par les femmes elles-mêmes, incluant celles des migrantes illégales, et l’action collective des regroupements qui luttent pour une reconnaissance du travail du sexe. Mais oui c’est un travail ! invite donc à déconstruire certains mythes et stéréotypes, et à étayer la preuve à l’effet qu’il est non seulement possible de défendre la légitimité du travail du sexe tout en luttant contre la violence, mais que cela est nécessaire.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; phi2030; philosophie; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution